Effects of a gel bait on the suppression of noxious Crematogaster rogenhoferi Mayr, 1879 (Formicidae: Myrmicinae) in Sri Lanka - R.K.S. Dias (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2019)
Crematogaster rogenhoferi Mayr, 1879 in a home garden in Sri Lanka was reported to cause health hazards and an investigation was conducted from February to November in 2016 to list the tree species bearing its nests and to record the nest structure, nest intensity and colony demography for the evaluation of its level of infestation and to recommend a method for the suppression of its population size. Three types of nests on 19 tree species were recognized. The largest nest had all life stages. The standard laboratory experiment conducted with the provision of 0.25 g of Optigard Ant Gel bait (OAG) showed 68% of mean mortality of workers. A field experiment conducted by applying separate 1 cm band of OAG and honey at 10 cm and 1 cm distance from three initial stage nests and a honey band only at 1 cm distance from three control nests recorded a significantly higher 89.2% of mean mortality of workers. Two mature nests treated with OAG similarly while two other similar nests served as simultaneous control nests resulted significantly higher 97.5% of mean mortality of workers and queens in OAG-treated nests, after 24 hours. Hence, application of 1 cm band of OAG on the tree trunk, if essential, is recommended as a method for suppressing the population size of C. rogenhoferi in a home garden.